Water permeability study of Membrane Electrode Assembly (MEA) fabrication using X-Y robotic sprayer machine - Kadhum, Abdul Amir H.; Mohamad, Abu Bakar; Wan Daud, Wan Ramli; Sitanggang, Ramli (2004)
The fabrication of MEA is conducted using an in-house robotic sprayer machine capable of adjusting its X-Y motions. The MEA produced was analyzed for porosity, distributions pore and water flux using BET and SEM based on the water permeability methodology. The results of the MEA shown that the pore geometry of MEA has a turtocity parameter which is greater than the MEA’s thickness while the permeability coefficient parameter of water is 9.10-5 gcm-1men–1psia-1 or the turtocity of 2. These results were then compared to the ones available from the commercial MEA.